Questões de prosódia: uma investigação, com apoio de instrumentais de análise fonético-acústica, dos padrões entoacionais de falantes bilíngües brasileiros e norte-americanos - Mauad, Sergio Augusto (2008)
This dissertation aims at investigating the prosodic patterns in the speech of bilingual American and Brazilian speakers. By means of acoustic phonetic analysis, the manner by which speakers structure the prosodic groups was investigated in light of models that underscore the discoursal and attitudinal functions of intonation. Analyses were carried out on various strands: pitch configurations in idioms, distribution of pitch accents within an utterance whether it be for contrastive or emphatic reasons, and loss of accentual prominence in words that are no longer part of the common ground between speaker and listener. The study involved 4 female subjects, two Brazilians and two Americans, in the 20-40 age group. The corpus is comprised of 7 sentences in English and in Portuguese, four of which were uttered in the declarative modality, one in the exclamative modality and two in the interrogative modality. The sentences were extracted from a dialogue so constructed as to allow for the expression of attitudes and emotions. The dialogue was read and interpreted in three repetitions. The recordings of the readings were carried out at PUC-SP´s Radio and TV studio. The acoustic analysis of the data was done by means of the PRAAT software program, whereby utterances were segmented into units of varying sizes: GIPC, vowels, syllables and consonants. Results point to the use of language-specific strategies by Brazilian and American speakers: (a) Brazilians seem to favor a greater number of prosodic groups in order to maintain sentence focus at terminals; (b) speakers of both languages are heavily influenced by L1 intonational patterns in YES/N0 questions; (c) idioms as produced by non-natives present pitch configurations which convey attitudes incongruent with their meanings in the target language; (d) there are major distributional differences in the two languages as regards nucleus focus; (e) shared information is not a strong enough reason for deaccenting in Portuguese